Envisioning our preferred future : new services, jobs, and directions - Eden, Bradford Lee (Creating the 21st-century academic library ;, 2016)
Volume 8 of the series Creating the 21st-Century Academic Library is focused on new services, directions, job duties and responsibilities for librarians in academic libraries of the 21st century. Topics include research data management services, web services, improving web design for library interfaces, cooperative virtual reference services, innovative uses of physical library spaces, uses of social media for disseminating scholarly research, information architecture and usability studies, the importance of special collections and archival collections, and lessons learned in digitization and.